Role of low-density lipoprotein electronegativity and sexual dimorphism in contributing early ventricular tachyarrhythmias following ST-elevation myocardial infarction - Wu, Mei-Yao; Lee, An-Sheng; Lin, Yen-Nien; Chung, Wei-Hsin; Chen, Ke-Wei; Lu, Chiung-Ray; Chen, Yun-Fang; Chang, Chia-Ming; Tsai, Wei-Chung; Shiao, Yi-Tzone; Chen, Chu-Huang; Chang, Kuan-Cheng (Frontiers in Cardiovascular Medicine, 2024)
Background: Early ventricular tachycardia/fibrillation (VT/VF) in patients with ST-elevation myocardial infarction (STEMI) has higher morbidity and mortality. This study examines gender-differentiated risk factors and underlying mechanisms for early onset VT/VF in STEMI. Methods: We analyzed data from 2964 consecutive STEMI patients between Jan 1, 2008 and Dec 31, 2021. Early VT/VF was defined as occurrence of spontaneous VT/VF of ≥30 seconds or requirement of immediate cardioversion/defibrillation within the first 48 hours after symptoms. An ex vivo ischemic-reperfusion experiments were conducted in 8-week-old ApoE-/- mice fed a high-fat diet to explore the underlying mechanisms of early VT/VF. Results: In 255 of out 2964 STEMI patients who experienced early VT/VF, the age was younger (58.6±13.8 vs. 61.0±13.0 years old, P=0.008) with a male predominance. The plasma levels of L5, the most electronegative subclass of low-density lipoprotein, was higher in early VT/VF patients compared to those without early VT/VF (n=21, L5: 14.1±22.6% vs. n=46, L5: 4.3±9.9%, P=0.016). In the experimental setup, all male mice (n=4) developed VT/VF post sham operation, whereas no such incidence was observed in the female mice (n=3). Significantly, male mice exhibited considerably slower cardiac conduction velocity as compared to their female counterparts in whole heart preparations (25.01±0.93 cm/s vs.42.32±5.70 cm/s, P<0.001), despite analogous action potential durations. Furthermore, isolated ventricular myocytes from male mice showed a distinctly lower sodium current density (-29.20±3.04 pA/pF, n=6) in comparison to female mice (-114.05±6.41 pA/pF, n=6, P<0.001). This decreased sodium current density was paralleled by a reduced membrane expression of Nav1.5 protein (0.38±0.06 vs. 0.89±0.09 A.U., P<0.001) and increased cytosolic Nav1.5 levels (0.59±0.06 vs. 0.29±0.04 A.U., P=0.001) in male mice. Furthermore, it was observed that the overall expressions of sorting nexin 27 (SNX27) and vacuolar protein sorting 26 (VPS26) were significantly diminished in male mice as compared to female littermates (0.91±0.15 vs 1.70±0.28, P=0.02 and 0.74±0.09 vs 1.57±0.13, P<0.01, respectively). Conclusions: Our findings reveal that male STEMI patients with early VT/VF are associated with elevated L5 levels. The gender-based discrepancy in early VT/VF predisposition might be due to compromised sodium channel trafficking, possibly linked with increased LDL electronegativity.